The therapeutic potential of exercise and caffeine on attention-deficit/hyperactivity disorder in athletes - Sogard, Abigail S.; Mickleborough, Timothy D. (Frontiers in Neuroscience, 2022)
Attention-deficit/hyperactivity disorder (ADHD) is characterized by evident and persistent inattention, hyperactivity, impulsivity, and social difficulties and is the most common childhood neuropsychiatric disorder, and which may persist into adulthood. Seventy to 80% of children and adults with ADHD are treated with stimulant medication, with positive response rates occurring for both populations. Medicated ADHD individuals generally show sustained and improved attention, inhibition control, cognitive flexibility, on-task behavior, and cognitive performance. The ethics of ADHD medication use in athletics has been a debated topic in sport performance for a long time. Stimulants are banned from competition in accordance with World Anti-Doping Association and National Collegiate Athletic Association regulations, due to their ability to not only enhance cognitive performance but also exercise performance. Limited research has been conducted looking at the differences in exercise performance variables in unmedicated ADHD verses medicated ADHD. Not all ADHD athletes choose stimulant medication in their treatment plan due to personal, financial, or other reasons. Non-stimulant treatment options include non-stimulant medication and behavioral therapy. However, the use of caffeinated compounds and exercise have both independently been shown to be effective in the management of ADHD symptoms in human studies and animal models. This mini review will discuss the effect of exercise and caffeine on neurobehavioral, cognitive, and neurophysiological factors, and exercise performance in ADHD athletes, and whether exercise and caffeine should be considered in the treatment plan for an individual with ADHD.